RANCANG BANGUN E-CATALOG GUNA MENINGKATKAN LAYANAN KUALITAS PROMOSI BERBASIS WEB (KASUS: BAKPIA MINO 904 YOGYAKARTA) - Jeffry Andhika Putra; Agus Rahmanto (Universitas Janabadra, 2020)
One of the uses of digital media is e-Catalog, where this media provides various information including lists and product price information. With e-Catalog, disseminating information about a product is easier. One of them is Bakpia which is one of the specialties originating from the Special Region of Yogyakarta. Along with the times, there are many new flavors of bakpia. The purpose of this research is to introduce Bakpia Mino 904 Minomartani using E-Catalog media, including introducing processed bakpia using e-Catalog media, as well as allowing customers to get available product information and making it easier for customers to place product orders online with the HTML, PHP, MySQL platforms., as well as Appserv. The results show that with this system, Bakpia Mino 904 is better known, makes it easier for consumers to order products online, and saves costs in terms of product promotion. Keywords: e-Catalog, Bakpia, Information Technology, MySQL, Appserv.